A New Spectral on the Gradient Methods for Unconstrained Optimization Minimization Problem - Hassan, Basim A.; Jabbar, Hawraz N. (Sulaimani Journal for Pure and Applied Sciences, 2020)
One simple and well-known method for minimizing the functions is a spectral conjugate gradient method. In this paper, we derive a new spectral on the method of gradient, which can give a new path of search. The new spectral method holds the property of descent and we have shown that the spectral method is convergent globally. The empirical results show that for the test problems, the given approach is competitive with the other conjugate gradient methods.
Keywords: Unconstrained Optimization; Conjugate Gradient Methods; Large Scale Methods